CeO2-modified Au@SBA-15 nanocatalysts for liquid-phase selective oxidation of benzyl alcohol. Issue 17 (11th February 2015) - Wang, Tuo; Yuan, Xiang; Li, Shuirong; Zeng, Liang; Gong, Jinlong
Abstract : This paper describes the design of Au–CeO2 @SBA-15 catalysts with improved catalytic activity and stability compared with Au@SBA-15 and Au/CeO2 due to the existence of large quantities of Au–CeO2 interfaces as well as the nanoconfinement effect of mesoporous SBA-15. Abstract : Tuning the interfacial perimeter and structure is crucial to understanding the origin of catalytic performance. This paper describes the design, characterization, and application of CeO2 modified Au@SBA-15 (Au–CeO2 @SBA-15) catalysts in selective oxidation of benzyl alcohol. The reaction results showed that Au–CeO2 @SBA-15 catalysts exhibited higher catalytic activity compared with Au@SBA-15 and Au/CeO2 catalysts under identical conditions along with the high selectivity towards benzaldehyde (>99%). The turnover frequency of benzyl alcohol over the Au–100CeO2 @SBA-15 catalyst is about nine-fold and four-fold higher than those of Au@SBA-15 and Au/CeO2 catalysts, respectively. The supported catalysts were characterized by N2 adsorption–desorption, inductively coupled plasma optical emission spectroscopy, X-ray diffraction, transmission electron microscopy, high-angle annular dark-field scanning transmission electron microscopy, scanning transmission electron microscopy-energy dispersive spectrometry, and X-ray photoelectron spectroscopy. It was found that the Au and small CeO2 nanoparticles (∼5 nm) were homogeneously mixed in the channels of SBA-15, which led to an increase in the interfacial area between Au and CeO2 and consequently a better catalytic performance of Au–CeO2 @SBA-15 catalysts for the selective oxidation of benzyl alcohol to benzaldehyde compared with that of Au/CeO2 . The prevention of agglomeration and leaching of Au nanoparticles by restricting them inside the mesopores of SBA-15 was conducive to the stable existence of large quantities of Au–CeO2 interface, which leads to high stability of the Au–CeO2 @SBA-15 catalyst.